Potential psychosocial impact of COVID-19 on children: a scoping review of pandemics and epidemics - Kaitlyn A Merrill; Trevyna NN William; Kayla M Joyce; Leslie E Roos; Jennifer L Protudjer (Journal of Global Health Reports)
# Background